SICLOO : APLIKASI PENGELOLAAN LIMBAH FASHION BERBASIS CIRCULAR ECONOMY SEBAGAI UPAYA MENDORONG 12 SDGS RESPONISBLE, CONSUMPTION, PRODUCTION DI KOTA TASIKMALAYA - Ocktapiana Aulia; Benyamin Hartanto; Carin Manisha Puteri; Lili Latifah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The increasing public interest in the fashion industry, also increases textile waste originating from clothing that is no longer used. The fast production carried out by fast fashion brands also adds to the environmental pollution. The use of the concept of changing clothes is an effort that can be made to overcome the problem of waste accumulation caused by fast fashion while making production in the economic flow more efficient. Based on the results of research on women aged 20-29 years in Tasikmalaya, it shows that Sicloo with circular economy concept can help women change clothes by paying low costs to buy clothes.